Development of In-Pipe Robot D300: Cornering Mechanism - Ana Sakura, Zainal Abidin; Sim, Chia Chie; Muhammad Hamizan, Zaini; Muhammad Farhan Aiman, Mohd Pauzi; Mohammad Muaz, Sadini; Shahrol, Mohamaddan; Annisa, Jamali; Rasli, Muslimen; Muhd Fadzli, Ashari; Mohd Syahmi, Jamaludin (EDP Sciences, 2017)
Utilization of robots for in-pipe maintenance considered as one of the most effective ways to improve the pipeline operation. The specific condition and structure of a pipeline system is a challenge for the robots to perform its task. This research aims to assess the characteristic and performance of the in-pipe robot in a 90° pipe elbow. Hence, a prototype of in-pipe robot for 300 mm UPVC pipe diameter (IPR-D300) has been built. The conception of the robot is based on wall-pressed caterpillar type which is suitable for not only horizontal pipeline position, but also vertical and elbows pipeline. This robot is equipped with ultrasonic sensors, high performance microcontroller board and powerful geared motor for travelling in the corner of pipeline. The developed IPR-D300 consist of three independent driving modules that are able to alter the speed according to the pipeline characteristic. The hardware and software of the IPR-D300 performance have been tested and successfully perform the cornering task smoothly. The developed IPR-D300 potentially can be applied for in-pipe cleaning operation especially on centralised sewerage system. As standard pipeline size for sewerage system housing in Malaysia is 200 mm, smaller and robust in-pipe robot will be the future target.